Signaling Pathway of GP88 (Progranulin) in Breast Cancer Cells: Upregulation and Phosphorylation of c-myc by GP88/Progranulin in Her2-Overexpressing Breast Cancer Cells - Wes E. Kim (Breast Cancer: Basic and Clinical Research, 2015)
Her2 is a receptor tyrosine kinase overexpressed in 25% of breast tumors. We have shown that the 88 kDa autocrine growth and survival factor GP88 (progranulin) stimulated Her2 phosphorylation and proliferation and conferred Herceptin resistance in Her2-overexpressing cells. Herein, we report that GP88 stimulates c-myc phosphorylation and upregulates c-myc levels in Her2-overexpressing cells. c-myc phosphorylation and upregulation by GP88 were not observed in non-Her2-overexpressing breast cancer cells. c-myc activation was inhibited upon treatment with ERK, PI3 kinase, and c-src pathway inhibitors, U0126, LY294002, and PP2. GP88 also stimulated c-src phosphorylation, a known upstream regulator of c-myc. Thus, we describe here a signaling pathway for GP88 in Her2-overexpressing cells, with GP88 stimulating Src phosphorylation, followed by phosphorylation and upregulation of c-myc. These data would suggest that targeting GP88 could provide a novel treatment approach in breast cancer.